Impact of Road Cuts in Slope Stability in Hilly Regions of Nepal - Shrestha, Jagat Kumar (Journal of Advanced College of Engineering and Management, 2021)
This paper reviews the geological and engineering aspects of rural road construction in the hilly areas of Nepal. The general background in geological, climatic and geographical setting is briefly presented in reference to the five-zone Himalayan model for the Nepal Himalayas. Then, alignment selection of rural roads is discussed in the context of the five zone mountain model. The impact of road cross section design and construction on mountain slopes has been studied. The cut width is a key geometric design parameter that has a significant impact on slope stability and volume of excavation. The choice of cut width in cross-section is reviewed and appropriate cut width in cross-section is recommended in terrain slopes to minimize slope failures and volume of excavation.